The third globalization can wealthy nations stay rich in the twenty-first century? - Breznitz, Dan; Zysman, John (Oxford University Press, 2013)
Given the powerfully negative and ongoing impact of the Great Recession on Western economies, the question of whether historically wealthy nations - the US, Western European countries, Japan - can stay wealthy has become an overriding concern for virtually every interested observer. In this work eminent political economists Dan Breznitz and John Zysman gather some of the discipline's leading scholars to assess the prospects for growth and prosperity among advanced industrial nations.